Reducing the vulnerability of women rural producers to rising hydro-meteorological disasters in Senegal: are there gender-specific climate service needs? - Tall, Arame (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
The goal of my research is to investigate whether there is a need for gender-specific climate services in communities at risk of flooding, drought and other hydro-meteorological disasters that are on the rise in Africa since the mid-1990s. If there is a need, how can identifying these needs be incorporated into the design of gender-responsive adaptation policies that will serve to reduce the vulnerability of rural women producers towards rising climate-related shocks? Indeed, the past decade (1995-2005) has been characterized by increasing climate variability and more frequent extremes all over Africa (see fig. 1). Whether women’s specific vulnerability to these hazards could be mediated through an increased use of salient, timely and legitimate climate information is an important question to answer because this has critical implications for the climate research and development practice communities.